Blowout fracture-associated orbital cellulitis progressing to panophthalmitis: a case report - Atsuhide Takesue (BMC, 2021)
Abstract Background Parvimonas micra is known as a causative agent of chronic periodontal disease. This Gram-positive obligate anaerobic coccus was cultured from the ocular surface of blowout fracture-related orbital cellulitis progressing to panophthalmitis. Case presentation The patient was a woman in her fifties who had panic disorder and subsequently was a victim of domestic violence. These factors led to delayed consultation. At the initial visit to an ophthalmologist, the ocular surface of the right eye was covered with pus. Swelling of the upper and lower eyelids prevented the eyelid from closing and exophthalmos, severe corneal ulcer, panophthalmitis, and no light perception were observed. Head computed tomography revealed an old blowout fracture and chronic sinusitis with orbital cellulitis. P. micra were isolated from culture of pus samples from the sinus and from the ocular surface. Conclusions There is a possibility that P. micra invaded the orbit via the fragile bony site and caused orbital cellulitis, severe corneal ulcer, and panophthalmitis that required enucleation. In cases of coexisting old blowout fracture and chronic sinusitis, the chronic sinusitis should be treated as quickly as possible.